OBSERVASI PENGKAJIAN RESEP SECARA ADMINISTRATIF PADA APOTEK X DI KABUPATEN BADUNG - Putri, Putu Rika Jesika (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2020)
Prescription screening is one of pharmaceutical care standards in Pharmacy which regulated in Permenkes RI No. 73 Tahun 2016. The aim of this research is to know about the implementation of one pharmaceutical care standards which is presription screening in one of pharmacies in Badung Regency. This research is descriptive observational. Data collection was performed by means of a retrospective (drug prescription data in January-May 2020) in X Pharmacy at Badung Regency with a total sample of 70 prescriptions. Based on the result of administrative screening of prescription, the percentage of incompleteness prescription at pharmacy X are patient name 2,86%, patient  age 45,71%, gender 87,14%, body weight 97,14%, patient address 51,43%, doctor's license (SIP) 42,86%, phone number 14,28%, physician initial 40% and prescription date 7,14%. The doctor's prescription completeness has not fulfilled the administrative prescription completeness requirement according to Permenkes RI No. 73 of 2016.